Perancangan Arsitektur Website Desa Sebagai Media Informasi Dan Pelayanan Publik Menggunakan Togaf Adm Pada Desa Nazalou Alo’oa - Fatamn Juang Putra Waruwu; Harta Setia Gea; Aroli Mendrofa; Jurisman Waruwu (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
The village government of Nazolu Alo'oa currently faces challenges in distributing public information and providing administrative services effectively due to the lack of an integrated digital platform. This study aims to design an enterprise architecture for a village website that serves as a public information media and an independent administrative service platform using the TOGAF ADM (Architecture Development Method) framework. This study applies a qualitative-descriptive approach with the scope of the design limited to the Preliminary Phase, Phase A (Architecture Vision), Phase B (Business Architecture), Phase C (Information Systems Architecture), and Phase D (Technology Architecture). The result of this research is a comprehensive blueprint for the village website design that aligns village administrative governance processes with information technology. The design includes modeling target business processes (to-be), relational data architecture (tables for residents, letters, and news), functional application components with multi-level access (Admin and Residents), and supporting technology infrastructure specifications. The blueprint generated in this study is ready to be used as a structured foundational guide in the development, implementation, and digitalization phase of public services in Nazolu Alo'oa Village.